Membangun Loyalitas Pelanggan di Era Live Commerce: Model Experiential Marketing dan Customer Engagement pada TikTok Shop - Wisnu Mahendri; Muhammad Nurhidayat (STKIP MAJENANG, 2026)
Purpose: This study aims to analyze the effect of experiential marketing on customer loyalty, with customer engagement as a mediating variable, within the TikTok Shop live commerce environment. Method: A quantitative explanatory survey was conducted with 130 respondents who had purchased from TikTok Shop at least once in the previous three months. Data were collected via online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), with evaluation of both measurement and structural models. Findings: The results indicate that experiential marketing has a positive and significant direct effect on customer engagement and on customer loyalty. Customer engagement also positively and significantly influences customer loyalty. Moreover, customer engagement partially mediates the relationship between experiential marketing and customer loyalty, with a Variance Accounted For value of 46.7 percent. Conclusions: This study confirms that experiential marketing, implemented through sense, feel, think, act, and relate dimensions, enhances customer loyalty on TikTok Shop both directly and indirectly through increased customer engagement. The partial mediation suggests a dual loyalty-building mechanism: an immediate affective route and a longer-term relational route. Future research is recommended to employ longitudinal designs and examine other platforms and moderating variables.